Does Additional Income Matter? Analyzing the Effects of Financial Incentives and Attendance on Civil Servant Performance - Putri Ridhotul Uliyah; Nurmala (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2026)
The Regional Civil Service and Human Resource Development Agency (BKPSDM) of West Aceh Regency plays a strategic role in managing civil servants at the regional level. The performance of this institution is influenced by employee attendance (absenteeism) and additional employee income (TPP). However, preliminary observations indicate several issues, including suboptimal attendance levels and dissatisfaction with the TPP calculation system. There is also a mismatch between performance and the amount of TPP received, where employees with low attendance still receive relatively high TPP, while high-performing employees do not receive maximum benefits. This condition creates a perception of unfairness, which may reduce motivation and work ethic. This study aims to analyze the effect of attendance and TPP on employee performance at BKPSDM of West Aceh Regency. The research was conducted at the BKPSDM office, involving 54 employees as the sample. The variables examined include attendance, additional employee income, and employee performance. The results show that, partially, attendance has a significant effect on employee performance with a significance value of 0.037 (<0.05). TPP also has a significant partial effect on performance with a significance value of 0.000 (<0.05). Simultaneously, both variables have a significant effect on employee performance, as evidenced by the F-test with a significance value of 0.000 (<0.05). The combined influence of attendance and TPP on employee performance is 44.5%, while the remaining 55.5% is influenced by other factors outside the research model. Thus, both variables are proven to support the research hypothesis.